Forest regeneration on European sheep pasture is an economically viable climate change mitigation strategy. (8th October 2020) - O'Neill, Connie; Lim, Felix K S; Edwards, David P; Osborne, Colin P
Abstract: Livestock production uses 37% of land globally and is responsible for 15% of anthropogenic greenhouse gas (GHG) emissions. Yet livestock farmers across Europe receive billions of dollars in annual subsidies to support their livelihoods. This study evaluates whether diverting European subsidies into the restoration of trees on abandoned farmland represents a cost-effective negative-emissions strategy for mitigating climate change. Focusing on sheep farming in the United Kingdom, and on natural regeneration and planted native forests, we show that, without subsidies, sheep farming is not profitable when farmers are paid for their labour. Despite the much lower productivity of upland farms, upland and lowland farms are financially comparable per hectare. Conversion to 'carbon forests' is possible via natural regeneration when close to existing trees, which are seed sources. This strategy is financially viable without subsidies, meeting the net present value of poorly performing sheep farming at a competitive $4/tCO2 eq. If tree planting is required to establish forests, then ∼$55/tCO2 eq is needed to break-even, making it uneconomical under current carbon market prices without financial aid to cover establishment costs. However, this break-even price is lower than the theoretical social value of carbon ($68/tCO2 eq), which represents the economic cost of CO2 emissions to society. The viability of land-use conversion without subsidies therefore depends on low farm performance, strong likelihood of natural regeneration, and high carbon-market price, plus overcoming potential trade-offs between the cultural and social values placed on pastoral livestock systems and climate change mitigation. The morality of subsidising farming practices that cause high GHG emissions in Europe, whilst spending billions annually on protecting forest carbon in less developed nations to slow climate change is questionable.